Trabalhadores favelados': identificação da favelas e movimentos sociais no Rio de Janeiro e em Belo Horizonte - Oliveira, Samuel Silva Rodrigues de (2014)
This thesis analyses the process of identification of favelas and the appropriation of this process by the social movements of the workers from the favelas, which we will call them 'favelados workers'. In A invenção das favelas (2005), Valladares presents the favelas as a social representation of the twentieth century. Based on this analytical framework which is shared and discussed by other authors, the thesis constructed comparative scales between Rio de Janeiro and Belo HorizonteIn the first part of the thesis, it is proposed a way to understand this social representation as a result of an identification process. As noted by Noriel in L'Identification (2006), the modern state was one of the largest producers of identifying technologies and power strategies which aims to understand, to categorize and to govern the populations (population) in an specific territory. The thesis investigates how the state in Rio de Janeiro and Belo Horizonte produced the identification of favelas, outlining a speech and a power strategy on the poor territories through legislation, censuses and studies commissions. Analogies, particularities and exchanges established in the identification process are analyzed, by observing the formation of a social marginality rhetoric that has reproduced not only a social stigma, but also has generated opportunities of claiming for rights. The second part of the thesis analyses the movements of the favelados workers, formed by the Favelados Workers Union (UTF) in Rio de Janeiro and Favelados Workers Federation in Belo Horizonte' (FTFBH). It proposes a way to understand how these social movements have organized repertoires of collective action, how they have made electoral mobilization tying up to Lefts, and how they have proposed urban reform projects by appropriating the identification of favelas to claim for rights.